Ibn Sina's argument for the necessity of prophecy through the subordination of the existence of the universe - Yarali Kordfirozjaei (حکمت اسرا, 2020)
Ibn Sina's words refer to an argument for the necessity of prophecy that neither he nor other scholars and theologians have fully interpreted. This argument is based on: For the existence of the Prophet as a perfect human being. Since Ibn Sina has referred to the principle of argument and has brought all its principles and preconditions in his works, it can be attributed to him and according to the preconditions used in this argument, it can be argued on He called the necessity of prophecy by means of the transcendental (or: subordinate or: parasitic) nature of natural beings (or: the universe), or by the ultimate essence of the existence of the prophet, or by the occurrence of evil. In this argument, the existence of evil has become a fulcrum for proving the necessity of prophecy, and thus what has often been considered a challenge to religiosity has been used as an opportunity. According to the Qur'anic evidence and the narration of the evidence based on this argument, it can be considered inspired by Islamic teachings. In this article, we tried to interpret this argument rationally and analyze its principles.